Scanning electron microscopic comparison of endophallus of Apis cerana and Apis mellifera - Kumar, Neelima R; Sharma, Ruchi; Anudeep, Anudeep (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> During the present investigations, the detailed morphoarchitecture of the male genitalia viz., the endophallus of the drone of A.cerana F. and A.mellifera L. was scanned under the electron microscope. Endophallus of each species was studied for its unique characteristics. Significant interspecific differences were observed in the 2 different species. These differences highlight the reproductive isolation in the genus. These species specific differences in the endophallus are highlighted in the paper.